Hubungan Pola Asuh Dengan Karakter Berwirausaha Pada Lulusan Perguruan Tinggi di Indonesia - Nurul Fadhilah Khair; Risanita Fardian Farid; Welan Mauli Anggun (Psyche 165 Journal, 2021)
Relationship of Parenting Patterns With Entrepreneured Characters Graduations In Indonesia. There has been an increase in the number of educated unemployed who come from college graduates (diploma & bachelor degree), making the government encourage graduates to become entrepreneurs with various facilities and policies. However, not everyone has the will and ability to be entrepreneurial. The creation of entrepreneurship is not only influenced by environmental support, personal characteristics today are considered a significant variable influencing the creation of entrepreneurship. It is known that positive parenting that provides proper autonomy to children is related to the independent, courageous, and creative character that characterizes entrepreneurship. This study aims to determine whether the (authoritative) parenting style is positively related to the entrepreneurial character of Indonesian university graduates. This study is a non-experimental correlational quantitative survey method using entrepreneurial character measurement using the Entrepreneurial Scale (SK-WIRA) and Parenting Patterns using the Parenting Authoritative Questionnaire (PAQ) . It was found that there was no significant negative relationship between authoritarian parenting and the entrepreneurial character of college graduates (p> 0.05). The null hypothesis is accepted and the alternative hypothesis is rejected.